Long‐term chronological changes in renal function and functional renal volume after nephron‐sparing surgery: A prospective observational study. (10th August 2021) - Onishi, Kenta; Tanaka, Nobumichi; Hori, Shunta; Miyake, Makito; Nakai, Yasushi; Anai, Satoshi; Hosokawa, Yukinari; Mibu, Hisakazu; Marugami, Nagaaki; Fujimoto, Kiyohide
Abstract : Objectives: To investigate long‐term chronological changes in functional renal volume and renal function after nephron‐sparing surgery, and factors that contribute to the progression of postoperative chronic kidney disease. Methods: A total of 80 patients who underwent nephron‐sparing surgery were enrolled in this prospective observational study. The renal function deterioration group was defined as patients whose estimated glomerular filtration rate at 5 postoperative years decreased by ≥20% relative to that before surgery. Results: The predicted estimated glomerular filtration rate, calculated based on the functional renal volume at 5 postoperative years, was strongly correlated with the postoperative estimated glomerular filtration rate (Spearman's ρ = 0.89, P  < 0.001). The rate of new‐onset stage IIIb chronic kidney disease was significantly higher in the renal function deterioration group than in the stable renal function group ( P  < 0.001). Multivariate analysis identified proteinuria ( P  = 0.017), small preoperative total functional renal volume (≤250 mL, P  = 0.046) and large tumor volume (≥4.5 mL, P  = 0.036) as independent factors associated with renal function deterioration. Conclusions: Our findings show that the functional renal volume is significantly associated with renal function, even in the long‐term postoperative period. Additionally, for patients with preoperative proteinuria, large tumor volume and small total preoperative functional renal volume, both oncological follow ups and medical interventions, including prevention of lifestyle‐related diseases, might prevent the progression of chronic kidney disease.